2007
DOI: 10.4088/pcc.v09n0305
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Bipolar Disorder Patients Misdiagnosed With Major Depressive Disorder

Abstract: Objective: Bipolar disorder is frequently misdiagnosed as major depressive disorder (MDD). We aim to quantify the prevalence of misdiagnosed bipolar disorder among the depression population and evaluate the quality-of-life (QOL) impact of misdiagnoses.Method: Data were collected from 2 selfadministered, cross-sectional studies in 2003. Patients participating in The Bipolar Disorder Misdiagnosis Study (N = 1156) were previously diagnosed with depression, experienced a depressive episode within the past year, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…The PGWBI is an instrument that is used to measure the balance between negative and positive emotional and affective conditions while avoiding references to physical symptoms of emotional distress. It has been widely tested in previous research in cardiovascular disease 36–40, 43 and in psychiatric patient populations 35, 41, 42, but has not been previously used to evaluate adults with rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PGWBI is an instrument that is used to measure the balance between negative and positive emotional and affective conditions while avoiding references to physical symptoms of emotional distress. It has been widely tested in previous research in cardiovascular disease 36–40, 43 and in psychiatric patient populations 35, 41, 42, but has not been previously used to evaluate adults with rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Psychological General Well Being Index (PGWBI)34 questionnaire is a validated instrument used to evaluate psychological distress in patients with non‐cancerous diseases 3, 35–43 and in those with cancer 44–46.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly pertinent to the study of bipolar disorder, given that patients with this illness experience depression more than hypomania or mania, 35,36 which may result in the misdiag nosis of bipolar depression as MDD, 37,38 suboptimal treatment and poor outcome. 39,40 Elucidating the neural correlates of social cognition may also assist in identifying the neuroanatomical basis of vulnerability to these disorders. Improved knowledge of the underlying neural mechanisms and nature of social cognitive deficits in patients with mood disorders may also assist in clarifying the nature of social dysfunction in patients with MDD and bipolar disorder and may aid in the development of psychologic interventions aimed at improving social perception and adjustment in these patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that patients with bipolar disorder, misdiagnosed with major depressive disorder, had a lower quality of life than patients correctly diagnosed with either major depressive disorder or bipolar disorder. 4 Previous studies have shown that patients with bipolar disorder, who had been misdiagnosed, received inappropriate and costly treatment regimens. 5,6 They also had higher medical costs than those recognized to have the condition.…”
mentioning
confidence: 99%